Possible role of lectins in mycoparasitism. - Elad, Y (1983)
Lectin activity in a host-mycoparasite relationship was demonstrated with Rhizoctonia solani and Trichoderma harzianum. Attachment of O but not A and B erythrocytes to hyphae occurred on R. solani but not on its mycoparasite. This phenomenon, which was Ca2+ and Mn2+ dependent, was prevented by galactose, present in T. harzianum cell walls, and by fucose.